Female paraurethral leiomyoma: treatment and long-term follow-up. Issue 12 (December 2015) - Migliari, Roberto; Buffardi, Andrea; Mosso, Luciano
Abstract Introduction We describe our experience with evaluating the ideal management of female paraurethral leiomyomas from imaging to surgery and follow-up. Methods Between January 2009 and January 2012, we treated six women (age range 32–49 years) affected by paraurethral leiomyoma of different sizes. Results All the six patients underwent transvaginal excision of the mass. They are free of recurrence at follow-up (range 32–72 months). Two patients developed stress urinary incontinence after the excision: in both cases, incontinence was corrected by a tension-free vaginal tape-obturator (TVT-O) placement. In one patient, a fascial sling was necessary to repair a urethral lesion that developed during surgical excision of the mass. Conclusion A well-defined protocol for diagnosing and managing a paraurethral mass had not been established as yet due the rarity of the mass. We suggest performing pelvic magnetic resonance imaging (MRI) as a primary examination, followed by lesion biopsy. Complete surgical resection performed transvaginally should be the treatment of choice. As paraurethral leiomyomas does not originate from intraurethral smooth-muscle component, urethral lesion is rare. Excision of female urethral leiomyoma transvaginally is safe, and postoperative urinary incontinence, if any, can be easily corrected with minimally invasive tecniques.